2018
DOI: 10.1021/acs.orglett.8b01300
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine as an Aryl C–H Activating Group

Abstract: The Pd-catalyzed regioselective C-H activation/arylation, /iodination, and/acetoxylation reactions of 4-arylpyrimidines using aryl iodides, N-iodosuccinimide, and (diacetoxyiodo)benzene respectively as coupling partners are described. Suzuki-Miyaura coupling and Sonogashira reactions of the resulting aryl iodides are demonstrated. The scalability of the C-H activation/functionalization starting with readily accessible 4-aryl pyrimidines is also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…4-Bromophthalimides 1a-c were prepared by using condensation reactions of 4-bromophthalic anhydridew ith the corresponding arylamine derivatives in DMF (1a [18] and 1c [19] are known compounds). We found that the 4-dimethylaminophthalimides 2a--c were produced as side-products in the reactions, respectively.I na ll cases,t hese substances can be separated by using column chromatography on SiO 2 .R egarding the mechanism of the formation of 2,w ep ropose that under reflux conditions DMF reacts with arylamine derivatives to liberate dimethylamine.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…4-Bromophthalimides 1a-c were prepared by using condensation reactions of 4-bromophthalic anhydridew ith the corresponding arylamine derivatives in DMF (1a [18] and 1c [19] are known compounds). We found that the 4-dimethylaminophthalimides 2a--c were produced as side-products in the reactions, respectively.I na ll cases,t hese substances can be separated by using column chromatography on SiO 2 .R egarding the mechanism of the formation of 2,w ep ropose that under reflux conditions DMF reacts with arylamine derivatives to liberate dimethylamine.…”
Section: Synthesismentioning
confidence: 99%
“…Phthalimide derivatives are promisinga so rganic optical materials. [15][16][17][18][19] These substances are thermally stable and capable of undergoing n-p*e lectronic transitions owing to the presence of carbonyl groups. Linked D-A-type phthalimidesa nd their p-extended derivatives can generate stable intramolecular charge-transfer( ICT) states, which are responsible for colour tuneable and highly efficient PL properties.I na ddition to their widely applicable opticalproperties, simple phthalimide derivatives are suitable to investigate the relation between their crystal structures and photochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The N ‐hydroxyimide/I 2 /hypervalent iodine oxidant system was suggested by Terent'ev and co‐workers for the iodo‐oxyimidation of styrenes ( 205 ) (Scheme 72). [152] It was demonstrated that a variety of nucleophiles might substitute for the iodine atom in the synthesized iodo‐oxyimides ( 207 ). The key attribute of the developed process was the non‐standard regioselectivity of C−I and C−O bond production, which suggested the radical reaction route.…”
Section: Applications Of Phenyliodine(iii)diacetatementioning
confidence: 99%
“…In various reported studies, the regioselectivities of C-H and C-H/C-H activations were controlled by DG such as monodentate amides [ 13 , 14 ], carboxylic acids [ 15 ], ketones [ 15 , 16 , 17 ], nitriles [ 18 , 19 ], aldehydes [ 15 , 20 ], phenols [ 21 , 22 ], esters [ 15 , 16 , 23 ], amides [ 15 , 16 ], N- methoxybenzamide [ 24 ], ureas [ 25 , 26 ], imines [ 27 , 28 ], hydrazines [ 29 , 30 ] and hydrazones [ 31 ], bidentate ligands [ 6 ], carbamates [ 32 ], sulfoxides [ 33 ], sulfonamides [ 34 , 35 ], sulfoximines [ 36 ], phosphine oxides [ 37 , 38 ], sulfides [ 39 ], thioamides [ 40 ] as well as some heterocycles such as purines [ 41 ], pyrimidines [ 42 ], pyrazoles [ 43 , 44 ], oxazolines [ 44 ], azoles [ 45 ], benzothiazoles [ 46 ], oxadiazoles [ 47 ], benzoxazoles [ 48 , 49 ] and 7-azaindole [ 50 ]. In some cases, heterocycles such as pyridine- N- oxide [ 51 ,…”
Section: Introductionmentioning
confidence: 99%